Molar mass and composition effects on the thermal stability of functional P(S-r-MMA) random copolymers for nanolithographic applications. Issue 5 (17th October 2017) - Antonioli, Diego; Gianotti, Valentina; Sparnacci, Katia; Laus, Michele; Clericuzio, Marco; Giammaria, Tommaso Jacopo; Seguini, Gabriele; Perego, Michele
Abstract : The thermal stability of P(S- r -MMA) random copolymers for BCP-based nanolithography is discussed with reference to molar mass and composition. Abstract : Functional hydroxyl-terminated poly(styrene- r -methyl methacrylate) (P(S- r -MMA)) copolymers (RCPs) are becoming key materials to control the substrate wetting characteristics not only for the conventional polystyrene- b -poly(methyl methacrylate) (PS- b -PMMA) block copolymers (BCPs) but also for high χ BCP systems. This paper reports the thermal stability of RCPs at fixed composition as a function of molar mass and at fixed molar mass as a function of composition. Distinct and sometimes opposite dependencies were observed when the samples were analyzed in bulk, in the form of thermally untreated thin films featuring different thicknesses and in the form of brush layers after the grafting process performed at different temperatures. The overall picture of these effects is useful for optimizing the thermal processing conditions of the various steps involved in BCP-based pattern transfer technology.